Death Due To Traumatic Asphyxia in Varanasi Region, India - Khalkho, Satish Kumar; Pathak, Manoj Kumar (International Journal of Medical Toxicology and Forensic Medicine, 2019)
Background: Traumatic asphyxia occurs when a powerful compressive force is applied to the thoracic cavity. This is most often observed in motor vehicle accidents, industrial and farming accidents, as well as the collapse of bridges, mansions, and during stampedes. Methods: During the period of October 2016 to May 2018, 33 cases of traumatic asphyxia were recorded in the Varanasi district autopsy center, i.e. the Department of Forensic Medicine, Institute of Medical Sciences, Banaras Hindu University, Varanasi, Utter Pradesh State, India. We conducted a prospective study on these incidents. Results: The incidence of traumatic asphyxia is irrespective of gender. However, men are more viable to it due to their outdoor activities. In the present study, males outnumbered females in the distribution of cases. The external and internal features in combination were congestion 26(78.8%), cyanosis 25(75.0%), and subconjunctival hemorrhage 10(30.3%). In the internal examination, rib fracture with flail chest was recorded in 5(15.2%) cases. Conclusion: Accidental death as a result of traumatic asphyxia is a major contributing factor to violent asphyxia. It results in asphyxia due to the compression of the chest by an external powerful compressive force.